CDN1163 alleviates SERCA2 dysfunction-induced pulmonary vascular remodeling by inhibiting the phenotypic transition of pulmonary artery smooth muscle cells - Weimin Yu; Qian Zhang; Yixiang Qiu; Hui Chen; Xiaoyang Huang; Li Xiao; Gang Xu; Siqi Li; Pingping Hu; Xiaoyong Tong (Clinical and Experimental Hypertension, 2023)
ABSTRACTBackground and Purpose Substitution of Cys674 (C674) in the sarcoplasmic/endoplasmic reticulum Ca2+ ATPase 2 (SERCA2) causes SERCA2 dysfunction which leads to activated inositol requiring enzyme 1 alpha (IRE1α) and spliced X-box binding protein 1 (XBP1s) pathway accelerating cell proliferation of pulmonary artery smooth muscle cells (PASMCs) followed by significant pulmonary vascular remodeling resembling human pulmonary hypertension. Based on this knowledge, we intend to investigate other potential mechanisms involved in SERCA2 dysfunction-induced pulmonary vascular remodeling.Experimental Approach Heterozygous SERCA2 C674S knock-in (SKI) mice of which half of cysteine in 674 was substituted by serine to mimic the partial irreversible oxidation of C674 were used. The lungs of SKI mice and their littermate wild-type mice were collected for PASMC culture, protein expression, and pulmonary vascular remodeling analysis.Results SERCA2 dysfunction increased intracellular Ca2+ levels, which activated Ca2+-dependent calcineurin (CaN) and promoted the nuclear translocation and protein expression of the nuclear factor of activated T-lymphocytes 4 (NFAT4) in an IRE1α/XBP1s pathway-independent manner. In SKI PASMCs, the scavenge of intracellular Ca2+ by BAPTA-AM or inhibition of CaN by cyclosporin A can prevent PASMC phenotypic transition. CDN1163, a SERCA2 agonist, suppressed the activation of CaN/NFAT4 and IRE1α/XBP1s pathways, reversed the protein expression of PASMC phenotypic transition markers and cell cycle-related proteins, and inhibited cell proliferation and migration when given to SKI PASMCs. Furthermore, CDN1163 ameliorated pulmonary vascular remodeling in SKI mice.Conclusions and Implications SERCA2 dysfunction promotes PASMC phenotypic transition and pulmonary vascular remodeling by multiple mechanisms, which could be improved by SERCA2 agonist CDN1163.